DMA Master Curves for Long-Term Life Prediction of Epoxy Resins and Composites Using Time Temperature Superposition - Thiago F. Silvano; Ricardo M. Di Benedetto; Marilia Sonego; Angelo Souza; Antonio C. Ancelotti Junior (Materials Research)
This study presents the results of constructing the master curve through dynamic mechanical analysis (DMA) of unidirectional composites made of glass fiber and epoxy resins of classes F and H to evaluate the thermal stability and durability of these materials. For this purpose, the viscoelastic behavior of the polymers and composites was evaluated using the time-temperature superposition (TTS) model, applying the empirical Sigmoidal equation and the Williams-Landel-Ferry (WLF) method to estimate the behavior at different temperatures. This approach allows the extension of experimentally accessible frequencies and the description of the entire relaxation behavior of the polymers. The time-temperature shift factor was determined from the DMA curves, generated from individual isotherms at different oscillation frequencies. It was observed that the viscoelastic behavior depends on both frequency and temperature, with a general equivalence between the behavior related to frequency and temperature during the transition processes. The composite materials manufactured by filament winding were also subjected to physical and thermal characterization through differential scanning calorimetry (DSC) and DMA, ensuring the consistent quality of high-performance structural composites. Once the time-temperature shift factors were described by the model, the master curve could be extrapolated to any desired temperature, reducing the need for extensive empirical testing.